Reclaiming fertility awareness methods to inform timed intercourse for HIV serodiscordant couples attempting to conceive. Issue 1 (9th January 2015) - Liao, Caiyun; Wahab, Maybel; Anderson, Jean; Coleman, Jenell S
Abstract : Introduction: Increased life expectancy of HIV‐positive individuals during recent years has drawn attention to their quality of life, which includes fulfilment of fertility desires. In particular, heterosexual HIV serodiscordant couples constitute a special group for whom the balance between desired pregnancy and the risk of viral transmission should be carefully considered and optimized. Although advanced assisted reproductive technologies are available, such treatments are expensive and are often unavailable. Moreover, standard viral load testing and antiretroviral therapy may not be accessible due to structural or individual barriers. To reduce the risk of HIV transmission, a lower cost alternative is timed condomless sex combined with other risk‐reduction strategies. However, timed condomless sex requires specific knowledge of how to accurately predict the fertile window in a menstrual cycle. The aim of this study was to summarize inexpensive fertility awareness methods (FAMs) that predict the fertile window and may be useful for counselling HIV‐positive couples on lower cost options to conceive. Methods: Original English‐language research articles were identified by a detailed Medline and Embase search in July 2014. Relevant citations in the included articles were also retrieved. Results and discussion: Calendar method, basal body temperature and cervicovaginal mucus secretions are the most accessible and sensitive FAMs, although poor specificity precludes their independent use in ovulation detection. In contrast, urinary luteinizing hormone testing is highly specific but less sensitive, and more expensive. To maximize the chance of conception per cycle, the likelihood of natural conception needs to be assessed with a basic fertility evaluation of both partners and a combination of FAMs should be offered. Adherence to other risk‐reduction strategies should also be advised, and timely referral to reproductive medicine specialists is necessary when sub/infertility is suspected. Conclusions: FAMs provide effective, economical and accessible options for HIV serodiscordant couples to conceive while minimizing unnecessary viral exposure. It is important for health care providers to initiate conversations about fertility desires in HIV‐positive couples and to educate identified couples on safer conception strategies.